The Strategic Role of Digital Innovation and Agility in Sustainable Organizations through Performance - Ayatulloh, Ayatulloh; Maliki, Budi Ilham; Komarudin, Mamay (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Bureaucratic transformation in the digital era requires public organizations to adopt innovation and digital agility to improve performance effectiveness and organizational sustainability. This study examines the impact of innovation and digital agility on employee performance and their implications for organizational sustainability, using the Cilegon City DPRD Secretariat as a case study. This study employed a quantitative approach with a survey method. Data were obtained from 93 employees of the Cilegon City DPRD Secretariat through a census questionnaire. Analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Construct validity was tested using factor loadings, while hypotheses were tested using t-statistics and p-values. The results show that innovation (t=5.293; p<0.05) and digital agility (t=3.649; p<0.05) significantly influence employee performance. Employee performance also mediates the relationship between the independent variables and organizational sustainability. The highest indicator of innovation is